GOOD’S SYNDROME WITH INCREASING γδ T-LYMPHOCYTE SUBPOPULATION: CASE REPORT - Tadić, Dragana; Tadić, Dragana; Marković, Olivera; Kraguljac-Kurtović, Nada; Kraguljac-Kurtović, Nada; Drobnjak, Olika; Drobnjak, Olika (Vojnosanitetski pregled, 2015)
Background: Good’s syndrome is a rare cause of adult-onset immunodeficiency associated with thymoma. Case report: We present 56-year-old men in whom Good’s syndrome has been diagnosed after two-year history recurrent infections. Examination of immune status of patient showed decreased serum levels of all immunoglobulins. Flow cytometry of peripheral blood lymphocyte revealed markedly reduced of peripheral B cells, CD4 T-cell lymphopenia, inverted CD4/CD8 T cell ratio 0,37 (CD4 20.82%, CD8 70.7%). Analysis of the subpopulations of T lymphocytes showed relative increasing of γδTCR T lymphocytes. Computed tomography scan of the chest showed a mediastinal mass compatible with thymoma diameter of 40mm. After initiation of intravenous immunoglobulins the patient is in the good clinical condition and without bacterial complications. As the patient refused the operative treatment we continue to control the mediastinal tumor mass which did not increase during the three-year follow-up. Conclusion: Good’s syndrome should be considered in patients older than 40 years with history of frequent infections. An abnormal immunoglobulin profile needs further investigation and flow cytometry which is crucial for establishing the diagnosis of Good’s syndrome. Our patient had typical immunological finding for Good’s syndrome, but also an increase of γδ TCR T lymphocyte subpopulation for which it is difficult to determine whether this is pathogenetic or secondary reactive event. Uvod: Good-ov sindrom je redak oblik imunodeficijencije kod odraslih udružene sa timomom. Prikaz bolesnika: Mi prikazujemo bolesnika starosti 56-godina kod koga je postavljena dijagnoza Good-ovog sindroma posle dvogodišnjeg perioda ponavljanih infekcija. Imajući u vidu smanjen nivo svih imunoglobulina u serumu uradjena je protočna citometrija limfocita periferne krvi. Ovom metodom utvrdjeno je potpuno odsustvo B ćelija, CD4 limfopenija, inverzan odnos CD4/CD8 T ćelija - 0,37 (CD4 20.82%, CD8 70,7%). Analiza subpopulacija T limfocita pokazala je relativno povećanje γδTCR T limfocita. CT pregledom grudnog koša vidjena je medijastinalna tumorska masa koja odgovara timomu prečnika 40mm. Posle započinjanja lečenja mesečnom primenom intravenskih imunoglobulina došlo je do značajne redukcije infektivnih komplikacija. S obzirom da je pacijent odbio operativno lečenje nastavljeno je CT praćenje medijastinalne tumorske mase koja se nije povećala tokom trogodišnjeg perioda. Zaključak: Na Good-ov sindrom treba misliti kod bolesnika starijih od 40 godina sa istorijom čestih infekcija. Smanjenje koncentracije imumoglobulina u serumu zahteva dalje ispitivanje uključujući protočnu citometriju koja je od ključnog značaja za postavljanje dijagnoze Good-ovog sindroma. Kod našeg bolesnika je protočnom citometrijom utvrdjen je nalaz tipičan za Good-ov sindroma, ali je registrovano i povećanje subpopulacije γδ TCR T limfocita za koje nije jasno da li je patogenetski ili reaktivni događaj.